RECONSTRUCTION OF AMINO ACID SEQUENCES OF CYCLIC PEPTIDES FROM THEIR MASS SPECTRA - E. S. Fomin (Вавиловский журнал генетики и селекции)
Mass spectrometry is a physical method, which can be applied to the investigation of proteomes of different organisms. It allows us both to solve the problem of identification of biological macromolecules and to sequence peptide chains in cases where information on the genomes is scarce or absent. Currently, there are many software programs to support research in this area. Nevertheless, in spite of all efforts, there is little progress in the development of programs able to solve the problem for de novo sequencing of cyclic peptides, which are most effective antibiotics, antitumor agents, immunosuppressants, toxins, and a vast number of nonribosomal peptides with unknown functions. In this paper, an effective algorithm for solving the problem of de novo sequencing cyclic peptides is proposed. The algorithm allows us to reconstruct sequences of lengths up to 160 amino acid residues.